A educação das relações étnico-raciais no ensino de arte a partir de uma perspectiva intercultural - Breda, Patricia Rodrigues (2023)
This dissertation addresses "The education of ethnic-racial relations in art teaching from an intercultural perspective", investigating, from the perspective of critical interculturality, how the Art textbook - Teacher's Manual, intended for the 5th grade of elementary school and used in the municipal network of Rio Claro-SP, acts for the education of ethnic-racial relations. The specific objectives are to Analyze whether the textbook recognizes and demystifies black and indigenous subjects; Verify whether the textbook contributes to promoting public policies to combat racism and provide racial equality, recognizing the social movements linked to black and indigenous subjects; Ascertain whether the textbook values knowledge that is not based on a Eurocentric perspective; Examine whether the socio-educational practices proposed in the textbook modify the usual dynamics of educational processes. The literature review was based on authors who discuss themes involving "art teaching", "ethnic-racial relations" and "indigenous culture". The theoretical bases that make up the framework used have critical interculturality as their central axis, based on the book entitled "Intercultural Critical Didactics: Approaches", organized by Vera Maria Candau. The research uses the qualitative paradigm, using documentary analysis as a method and the content analysis technique for data processing, through the investigation of textbooks, with the aim of understanding whether there is an approach to the education of ethnic-racial relations from a critical intercultural perspective. The general conclusion reached through the analysis of the data is that black people and their culture are present in the book and are not in a "tribal" or folklorized conception - which can already be seen as a step forward. However, we need to go further and approach these black identities and cultures from an anti-racist perspective. When it comes to indigenous peoples, their cultures do not appear in textbooks. In order for this situation to change, it is necessary for the curriculum of undergraduate courses to be altered - including education for ethnic-racial relations - for schools and universities to develop partnerships and for teachers to be provided with ongoing training involving these issues.